The utility of the zero-inflated Poisson and zero-inflated negative binomial models: a case study of cross-sectional and longitudinalDMFdataexamining the effect of socio-economic status - Lewsey JD, Thomson WM. (Blackwell Synergy, 2004)
To examine the utility of the zero-inflated Poisson (ZIP) and zero-inflated negative binomial (ZINB) modelling approaches for modelling four sets of dental caries data from the same cohort study [with particular attention to the influence of childhood socioeconomic status (SES)]: cross-sectional data on the deciduous dentition at age 5 years; cross-sectional data on the permanent dentition at age 18 and 26 years; and longitudinal data on caries increment between ages 18 and 26 years.